Vitamin B12 Deficiency Among a Sample of Type 2 Diabetic Patients on Metformin in Erbil-City - Twana Mahmood Hamzah; Bushra Mohammed Ali (Advanced Medical Journal)
Background and objectives:Metformin is the most common oral hypoglycemic agent used as first line together with life style modification in almost all type 2 diabetes patients worldwide. The aim of the study was to determine the percentage of vitamin B12 deficiency in a sample of patients with type 2 diabetes mellitus and its association with the daily dose metformin (? 1.000 mg) and more than two years durations of treatment and anemia.